Optimizing parameters of robotic task-oriented programming via a multiphysics simulation - Delledonne, Michele; Villagrossi, Enrico; Beschi, Manuel (Proceedings (IEEE International Conference on Emerging Technologies and Factory Automation), 2023)
The programming complexity of industrial robots significantly limits their expansion in complex industrial applications. Consequently, research has focused extensively on the development of intuitive programming methods.This article proposes a framework for task-oriented programming introducing an intuitive and modular task structure. The framework provides an algorithm able to optimize the execution parameter of the tasks. A physical simulation environment allows accurate parameter optimization in a virtual environment providing feasible and safe results. Efficiency tests demonstrated the method's effectiveness, and a comparison with genetic and Bayesian -based ones have been conducted.